Pam16 and Pam18 were repurposed during Trypanosoma brucei evolution to regulate the replication of mitochondrial DNA - von Känel, Corinne; Stettler, Philip; Esposito, Carmela; Berger, Stephan; Amodeo, Simona; Oeljeklaus, Silke; Calderaro, Salvatore; Durante, Ignacio M; Rašková, Vendula; Warscheid, Bettina; Schneider, André (PLoS biology, 2024)
Protein import and genome replication are essential processes for mitochondrial biogenesis and propagation. The J-domain proteins Pam16 and Pam18 regulate the presequence translocase of the mitochondrial inner membrane. In the protozoan Trypanosoma brucei, their counterparts are TbPam16 and TbPam18, which are essential for the procyclic form (PCF) of the parasite, though not involved in mitochondrial protein import. Here, we show that during evolution, the 2 proteins have been repurposed to regulate the replication of maxicircles within the intricate kDNA network, the most complex mitochondrial genome known. TbPam18 and TbPam16 have inactive J-domains suggesting a function independent of heat shock proteins. However, their single transmembrane domain is essential for function. Pulldown of TbPam16 identifies a putative client protein, termed MaRF11, the depletion of which causes the selective loss of maxicircles, akin to the effects observed for TbPam18 and TbPam16. Moreover, depletion of the mitochondrial proteasome results in increased levels of MaRF11. Thus, we have discovered a protein complex comprising TbPam18, TbPam16, and MaRF11, that controls maxicircle replication. We propose a working model in which the matrix protein MaRF11 functions downstream of the 2 integral inner membrane proteins TbPam18 and TbPam16. Moreover, we suggest that the levels of MaRF11 are controlled by the mitochondrial proteasome.
Keywords: molekulární evoluce; mitochondrie; Protozoan Proteins; DNA, Mitochondrial; protozoální proteiny; Trypanosoma brucei brucei; Mitochondrial Proteins; replikace DNA; DNA Replication; Mitochondria; mitochondriální proteiny; Evolution, Molecular; mitochondriální DNA